Outcomes of One straight‐line flow with and without pedal arch in patients with critical limb ischemia. Issue 1 (22nd October 2015) - Higashimori, Akihiro; Iida, Osamu; Yamauchi, Yasutaka; Kawasaki, Daizo; Nakamura, Masato; Soga, Yoshimitsu; Zen, Kan; Yokoi, Yoshiaki; ,
Abstract : Objectives: This study aimed to compare the outcomes of revascularization strategies for patients with critical limb ischemia (CLI) whereby single vessel run off to the foot was established with or without flow into a patent pedal arch. Methods: We retrospectively analyzed data from 312 consecutive patients with CLI who underwent endovascular therapy (EVT) between December 2009 and February 2011. Below‐the‐knee angiography identified one vessel run off in 137 patients (44%), and we aimed to compare the outcomes between those patients where revascularization resulted in one‐straight‐line flow into a patent pedal arch (76 limbs, Group A) versus those who attained one straight‐line flow to the distal end of a tibial vessel without flow into a patent pedal arch (61 limbs, Group B). The study endpoints were amputation free survival rate, limb salvage rate and wound healing rate at 12 months after EVT. Results: Amputation free survival rate differed significantly between groups (88.2% in group A vs. 65.6% in group B, P = 0.01). Limb salvage rate also differed between groups (98.4% vs.89.3%, P = 0.03). Wound healing rate showed a trend towards difference between the two groups (89.4% vs. 80.6% P = 0.11). Conclusions: Among patients with CLI where only one vessel runoff can be established to the foot, direct flow into a patent pedal arch is essential to improve their clinical outcomes. © 2015 Wiley Periodicals, Inc.